Safe dose of intravitreal imatinib and its effect on laser-induced choroidal neovascularization: a rat-model experiment. Issue 1 (December 2015) - Nikkhah, Homayoun; Ahmadieh, Hamid; Ramezani, Alireza; Rezaei Kanavi, Mozhgan; Hosseini, Seyed; Sadeghi, Naficeh; Khandaghy Meybodi, Seyed; Yaseri, Mehdi
Abstract Background This two-phase experimental study was conducted to determine the maximum safe dose of intravitreal imatinib (IVI) and its inhibitory effect on a rat model of choroidal neovascularization (CNV). Methods In phase I, 60 rats were divided into six groups (A to F); five of which received IVI with concentrations of 330 (A), 250 (B), 165 (C), 80 (D), and 40 (E) µg/5 µl, and the control group (F) received balanced salt solution (BSS). In addition to electroretinography (ERG), routine histopathological analysis and immunohistochemistry for glial fibrillary acidic protein were performed. In phase II, CNV was induced by laser photocoagulation in 25 rats and the animals were divided into two groups. One group received the maximum safe dose of IVI, determined in phase I, and the other received intravitreal BSS. After 4 weeks, the groups were compared in terms of mean scores of fluorescein leakage in fluorescein angiography and the mean CNV areas in histopathological sections. Results In phase I, ERG and the histopathological findings revealed retinal toxicity in groups A to D and A to C, respectively; therefore, a dose of 40 µg/5 µl imatinib was specified as the maximum safe dose for phase II. In phase II, late phase fluorescein leakage and the CNV areas were not significantly different between the imatinib-treated eyes and the controls (p = 0.62 and p = 0.5, respectively). Conclusions Despite the safety of IVI with a dose of 40 µg/5 µl, no inhibitory effect on laser-induced CNV was observed. Further studies are required to investigate the possible synergistic effects of Imatinib with conventional anti-CNV drugs.